Responses to the Crisis of Neo-liberal Globalization: State Intervention in Palm Oil Production in Chiapas, Mexico - B. FLETES-OCÓN, HÉCTOR; BONANNO, ALESSANDRO (The International Journal of Sociology of Agriculture and Food, 2013)
Employing the case study of the cultivation of African palms for the production of palm oil in Chiapas, Mexico, this article probes the theme of alternative patterns of development to neo-liberal globalization. In particular, it discusses the issue of the return to state intervention (neo-Fordism) as an instrument to promote socio-economic development. Chiapas has been the theatre of the Zapatista movement of 1994. As a result of that popular uprising and despite its overtly neo-liberal posture, the Mexican state intervened significantly in Chiapas. In this context, the monoculture of the African palm has been pursued as a strategy to address local poverty among farmers, generate alternative and renewable forms of energy and provide a scheme for socio-economic growth in the area. This article illustrates the contradictory results of this ‘interventionist’ developmental project and the consequences and resistance that it entailed. The analysis of this case reveals the problematic nature of nation-state led interventionist schemes in a context marked by the emerging crisis of the neo-liberal model. It also underscores the significance of local initiatives that are generated by the aspirations and abilities of local residents.